MENGHITUNG KEBUTUHAN PENGERING GABAH DI KECAMATAN CIOMAS BOGOR DENGAN METODE MONTE CARLO - Manalu, Lamhot P. (Jurnal Sains dan Teknologi Indonesia, 2009)
Sun drying is the traditional method for drying and still preferred in Asia because cheap compared to mechanical drying. Since it uses the sun as heat source it is friendly to the environment, many farmers, grain collectors, traders and millersoften dry their paddy on pavements that specifically constructed for drying. Sundrying pavements have the advantages of high capacity and thus economics of scale, but the weakness is very dependent on the weather. The amount of paddy that can be dried with a drying depends on the number of sunny days, so it is important to know the probabilities of rainy day based on the historical climate data in a region. From these, simulations can be done to calculate how many dryer machines should be provided to overcome the lack of drying capacity. This methodis known as Monte Carlo. This paper presents a study to determine the amount mechanical dryer needed based on the failure probability of sun drying pavements using monte carlo simulation methods in the District of Ciomas, Bogor.The study results based on 10 years daily rainfall data the probability of rainy days in March (0.62) was greater than in September (0,37), so that the total capacity of dryer machine to be prepared is 110 tons/ day. That was equal to 11 units dryerswith 10 tons / unit in capacity.